Teaching Arabic At Rawda Al-Islamiyyah Secondary School/ تعليم اللغة العربية في مدرسة روضة الإسلامية الثانوية الأهلية - Ratu Noor Hamidah (Jurnal Al-Maqoyis, 2022)
This study focused on learning Arabic in the classroom, the purpose of this study was to determine the learning activities that took place at MAs Raudhatul Islamiyah. Qualitative descriptive research approach. The procedure for collecting data was observing, interviewing, and documenting. The subject of this research is Arabic teachers. In planning the management is carried out by the teacher, learning planning is by the learning administration flow. The steps in making the first learning administration Competency Standards, Basic Competencies, annual programs, semester programs, and Implementation Plans are more operational and detailed. In preparing the plan the teacher is given the freedom to change, modify, and adapt the syllabus to the conditions of the school, region, and the characteristics of the students so that it is more effective and efficient because it meets criteria such as pre-test, learning process, and post-test. Teachers master learning materials, various strategies, methods, and approaches that vary according to the material being studied, as well as strengthening student motivation by increasing awareness of the importance of learning Arabic in everyday life, giving praise and rewards, giving questions, assignments, tests and notifying results.